PERAN AKUNTAN DAN PERUSAHAAN MENUJU TUJUAN PEMBANGUNAN BERKELANJUTAN (SUSTAINABLE DEVELOPMENT GOALS / SDGs) 2030 - Budi Karyanto; Rina Martiana (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2020)
One of the most effective things in achieving sustainable development goals is utilizing and allocating taxes obtained by the government from companies for the development of remote areas that are still lagging behind.Therefore, the first thing that must be emphasized and done endlessly is to eradicate corruption, so that government funds can be used optimally for the purpose of sustainable development, alleviating all forms of wealth in all places that can be used for nutrition, and promoting sustainable agriculture. How to live a healthy and prosperous life, quality education, clean air and proper sanitation, decent work and economic growth, namely, sustainable and inclusive economic growth, employment and decent work for all. Until finally the infrastructure is strong, and its responsiveness is in the areas between the regions of this motherland.To achieve something in particular. The goal of sustainable development (SDGs) is not only the task of the government alone, but also the task of the whole world community, especially governments and companies (assisted by accountants) in their vision and mission to achieve SDGs. Through accountability, transparency and mutual trust and commitment from all parties, surely anything will be achieved